Outcomes of a Rapid Deployment Aortic Valve Versus Its Conventional Counterpart: A Propensity-Matched Analysis. Issue 3 (May 2018) - Wahlers, Thorsten C.W.; Andreas, Martin; Rahmanian, Parwis; Candolfi, Pascal; Zemanova, Barbora; Giot, Christophe; Ferrari, Enrico; Laufer, Günther
Abstract : Objective: The aim of this study was to compare outcomes after rapid-deployment aortic valve replacement (RDAVR) and conventional aortic valve replacement (AVR) from two studies. Methods: Patients who underwent RDAVR (INTUITY valve) in the prospective, 5-year, single-arm multicenter TRITON study, or conventional AVR (Perimount Magna Ease valve) in the prospective Perimount Magna Ease postmarket study, were propensity score matched and compared for procedural, hemodynamic, safety, and clinical outcomes. Results: Matched RDAVR (n = 106) and conventional AVR (n = 106) patients had similar baseline characteristics (mean ± SD age, 72.8 ± 7.6 vs 72.5 ± 7.4 years; male 59.4% vs 61.3%) and procedures (concomitant procedures: 41.5% vs 50.9%). Mean ± SD aortic cross-clamp time was significantly shorter in RDAVR than AVR patients (51.8 ± 20.9 vs 73.9 ± 33.2 minutes; P < 0.001), as was mean cardiopulmonary bypass time (82.8 ± 34.2 vs 102.4 ± 41.7 minutes; P < 0.001). At 1 year, RDAVR patients showed significantly lower mean ± SD and peak aortic valve gradients (9.0 ± 3.4 and 17.0 ± 6.2 mm Hg, respectively) than conventional AVR patients (13.4 ± 5.5 and 24.2 ± 10.8 mm Hg, respectively; all P < 0.001). Patient-prosthesis mismatch was significantly less common with RDAVR than with AVR [overall: 16/66 (24.2%) vs 46/76 (60.5%); P = 0.007; severe: 2/66 (3.0%) vs 13/76 (17.1%)]. There were no significant differences between the RDAVR and AVR groups regarding 30-day safety endpoints. Survival rates in the RDAVR and conventional AVR groups were, respectively, 99.1% and 100.0% at 30 days, 97.1% and 95.1% at 1 year, and 93.3% and 94.1% at 3 years ( P = nonsignificant). Conclusions: In this retrospective study with matched populations, the RDAVR with the INTUITY valve system provided superior procedural and hemodynamic outcomes than a standard bioprosthesis without compromising safety. Abstract : Supplemental digital content is available in the text.